Experiences of children (ages 6–12) during COVID‐19 pandemic from mothers' perspectives. Issue 2 (10th October 2021) - Akın Işık, Rabiye; Bora Güneş, Nebahat; Kaya, Yunus
Abstract: Purpose: This study evaluated the experiences of children between ages 6 and 12 based on their mothers' perspectives during the COVID‐19 pandemic. Methods: Ten mothers living in Ankara, Turkey with children in the aforementioned age range, participated in this study. Data were collected through focus group interview with a qualitative phenomenological approach followed by thematic data analysis. Findings: Three categories were obtained relating to the pandemic, including negative effects, positive effects, and the resultant needs and expectations of parents. Conclusion: The findings show that the pandemic has significantly affected children in psychological, social, developmental, and academic realms. Therefore, it is necessary to plan interventions with a multidisciplinary approach to increase children's physical and psychosocial health, minimizing children's level of negative influences.